2013
DOI: 10.1089/vbz.2012.1028
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofRickettsia parkerifrom within Piura, Peru, and the First Reported Presence ofCandidatusRickettsia andeanae in the TickRhipicephalus sanguineus

Abstract: Domestic farm animals (n = 145) were sampled for the presence of ectoparasites in northwestern Peru during March, 2008. Ninety domestic animals (62%) were positive for the presence of an ectoparasite(s) and produced a total collection of the following: 728 ticks [Amblyomma maculatum, Anocentor nitens, Rhipicephalus (Boophilus) microplus, Rhipicephalus sanguineus, and Otobius megnini], 12 lice (Haematopinus suis), and 3 fleas (Ctenocephalides felis). A Rickettsia genus-specific qPCR assay was performed on nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 9 publications
2
12
0
5
Order By: Relevance
“…However, recent studies identified dual and even triple rickettsial coinfections in questing ticks. A single D. variabilis tick collected in Ohio was found coinfected with Rickettsia bellii, R. montanensis, and R. rickettsii (Carmichael and Fuerst, 2010); two A. americanum collected in Kansas were concurrently infected by R. rickettsii and R. amblyommatis (Berrada et al, 2011); and two Peruvian A. maculatum were co-infected with both Candidatus R. andeanae and R. parkeri (Flores-Mendoza et al, 2013). In addition, laboratory-reared A. dubitatum were able to acquire and transmit R. rickettsii transstadially despite being 100% infected with R. bellii (Sakai et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies identified dual and even triple rickettsial coinfections in questing ticks. A single D. variabilis tick collected in Ohio was found coinfected with Rickettsia bellii, R. montanensis, and R. rickettsii (Carmichael and Fuerst, 2010); two A. americanum collected in Kansas were concurrently infected by R. rickettsii and R. amblyommatis (Berrada et al, 2011); and two Peruvian A. maculatum were co-infected with both Candidatus R. andeanae and R. parkeri (Flores-Mendoza et al, 2013). In addition, laboratory-reared A. dubitatum were able to acquire and transmit R. rickettsii transstadially despite being 100% infected with R. bellii (Sakai et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…'Candidatus Rickettsia andenae' is a spotted fever group agent infecting found infecting adults of A. parvum in Argentina (PACHECO et al, 2007), Brazil , A. maculatum in Unites States (PADDOCK et al, 2010;FORNADEL et al, 2011;JIANG et al, 2012;FERRARI et al, 2013;NADOLNY et al, 2014) and Peru (BLAIR et al, 2004;JIANG et al, 2005;FLORES-MENDOZA et al, 2013), Amblyomma pseudoconcolor Aragão, 1908in Argentina (TOMASSONE et al, 2010a, A. triste in Chile (ABARCA et al, 2012), A. sculptum in Brazil (WITTER et al, 2016), R. sanguineus (FLORES-MENDOZA et al, 2013), and Ixodes boliviensis Neumann, 1904(JIANG et al, 2005 in Peru. Nymphs of A. parvum collected from wild birds of were found infected with this Rickettsia in Paraguay , and in Brazil (LUGARINI et al, 2015) ( Table 1).…”
Section: Rickettsia Species Found In Ticks Parasitizing Birds In Brazilmentioning
confidence: 99%
“…Few years later, R. parkeri- infected A. triste ticks were reported in Brazil [5] and Argentina [6]. More recently, A. maculatum ticks were found infected by R. parkeri in Peru [7]. While a number of human cases of R. parkeri rickettsiosis have been recently described in the United States, all associated with A. maculatum ticks [2, 810], in South America, human cases were reported only in Uruguay and Argentina, generally associated with A. triste ticks [11, 12].…”
Section: Introductionmentioning
confidence: 99%